FAKTOR-FAKTOR YANG MEMPENGARUHI TERHADAP TIMBULNYA ACNE VULGARIS (JERAWAT) PADA REMAJA DI SMAN 1 PELANGIRAN KABUPATEN INDRAGIRI HILIR TAHUN 2018 - Asbullah Asbullah; Putri Wulandini; Yulia Febrianita (Jurnal Keperawatan Abdurrab, 2021)
Acne vulgaris is a chronic skin disease that occurs due to chronic inflammation of pilosebasea characterized by blackheads, papules, pustules, nodules and cysts in the predilection areas that are usually in the sebaceous glands such as face, chest and upper back. in adolescent acne incidence occurs with the age range 14-17 years in women, and in men the age range 16-19 years. factors influencing the occurrence of acne vulgaris is age factor, cosmetic usage factor and food factor. The purpose of this research is to know the factors that influence on the emergence of acne vulgaris (acne) in adolescents at SMAN 1 Pelangiran Year 2018. The research design used is cross sectional, where the research is in SMAN 1 Pelangiran. Population in this research is all student of SMAN 1 Pelangiran 177 people. Sample 122 respondents. The sample in this research is taken by using cluster sampling method. Data used primary data, research instrument in the form of questionnaire. Data were analyzed univariat and bivariate. The results of the study showed that the majority were at the age of 17 years, as many as 47 people (38.5%) .The majority of students who experienced the onset of Acne Vulgaris (acne) in adolescents at SMAN 1 Pelangiran had the habit of not using as many as 83 people (68, 0%). The majority of students who experienced the onset of acne vulgaris (acne) in adolescents at SMAN 1 Pelangiran Indragiri Hilir district has a habit of consuming bad food as much as 99 people (81.1%). It is expected that students will improve their knowledge of acne causing problems and improve self-hygiene behaviors to reduce the incidence of Acne Vulgaris, and be more concerned with health with the adoption of a healthy lifestyle that helps them to have a positive body image.